Impact of Middle Turbinectomy on Airflow to the Olfactory Cleft: A Computational Fluid Dynamics Study. Issue 3 (May 2019) - Alam, Suhyla; Li, Chengyu; Bradburn, Kathryn H.; Zhao, Kai; Lee, Thomas S.
Background: The impact of middle turbinate resection (MTR) on olfaction remains a point of debate in the current literature. Few studies have objectively evaluated olfactory cleft airflow following MTR; thus, the mechanism by which MTR may impact olfaction is poorly understood. It is not known whether the postsurgical changes in airway volume, flow, and resistance increase odorant transport or disrupt the patterns of normal airflow. Computational fluid dynamics can be used to study the nasal airway and predict responses to surgical intervention. Objective: To evaluate the functional impact of MTR on nasal airflow, resistance, and olfaction. Methods: Five maxillofacial computed tomography scans of patients without signs of significant sinusitis or nasal polyposis were used. Control models for each patient were compared to their corresponding model after virtual total MTR. For each model, nasal airway volume, nasal resistance, and air flow rate were determined. Odorant transport of 3 different odorants in the nasal cavity was simulated based on the computed steady airflow field. Results: Total airflow significantly increased following bilateral MTR in all patient models ( P  < .05). Consistent with our airflow results, we found a decrease in nasal resistance following MTR. MTR significantly increased area averaged flux to the olfactory cleft when compared to controls for phenylethyl alcohol (high-sorptive odorant). Results for carvone (medium sorptive) were similarly elevated. MTR impact on limonene, a low flux odorant, was equivocal. Conclusion: MTR increases nasal airflow while decreasing the nasal resistance. Overall, olfactory flux increased for high sorptive (phenylethyl alcohol) and medium sorpitve (l-carvone) odorants. However, the significant variation observed in one of our models suggests that the effects of MTR on the nasal airflow and the resultant olfaction can vary between individuals based on individual anatomic differences.